Synthesis and Characterization of PANi/PVA Nanofibers with Variation of Nozzle to Collector Distance Using Electrospinning Method - Nugrahani Primary Putri, Iddah Isroiyyah (Universitas Mataram, 2022)
FTIR confirmed fumaric acid doped polyaniline as a polyaniline emeraldine salt phase. This study aims to determine the value of the electrical conductivity of PANI/PVA with variation in the distance of the needle to the collector, namely 11 cm, 13 cm, 15 cm, and 17 cm. The electrospinning method was carried out on a PANI/PVA solution to form polyaniline nanofibers. The electrospinning solution used a percent ratio of 1:1 PANI/PVA (10%). The morphological and fiber properties were characterized using FTIR, optical microscope, and SEM-EDX. The number of threads decreases and becomes more delicate as the distance increases due to the evaporation of PVA. The diameter of PANI/PVA fiber and pure PVA fiber is 236 nm and 256 nm. The PVA fiber diameter is slightly larger thane PANI/PVA fiber. Electrical conductivity was carried out using the four-point probe method. The electrical conductivity of the PANI/PVA sample is 1.39 Ã— 10-6 S/cm at a distance of 15 cm with the best fiber shape. Â Â